Gait Kinematics and Spatiotemporal Variables after Enriched, Task-Specific Therapy in the Chronic Phase after Stroke. A Single-Subject Experimental Design Study - Vive, Sara; Zugner, Roland; Tranberg, Roy; Bunketorp-Kall, Lina (Archives of Clinical and Medical Case Reports, 2021)
Objectives: In this single-subject experimental design study, we investigated the effect of late-phase stroke rehabilitation on gait pattern. Methods: A subgroup from a previous clinical study, four men in the chronic phase after stroke, received 3 weeks of enriched and task-specific therapy (ETT) consisting of task-specific exercise, socialization, sensory and cognitive stimulation in a Mediterranean climate. Spatiotemporal gait variables, kinematics and symmetry were measured before and after the intervention in an advanced gait laboratory. Statistical significance was determined with the two-standard deviation band method. Results: Subject 1 had kinematic improvements (increased knee flexion during swing and dorsiflexion during stance) and spatiotemporal gains (increased speed, double-limb support, stride length and cadence) after ETT. Subject 2 had improved swing time symmetry ratio but no spatiotemporal or kinematic improvements. Subject 3 had gains in speed, stride width and length, and knee flexion during swing. Subject 4 had a change in cadence but no gain in kinematics, nor symmetry. Conclusions: Two of the four participants had significant improvements in gait kinematics, symmetry, and spatiotemporal variables after the intervention. Future research should consider the potential effects of ETT with the aim of validating the conclusions that can be drawn from this study.